Caracterização molecular e preservação de isolados de bactérias diazotróficas associadas ao arroz - Pereira, Jonalda Cristina dos Santos (2021)
Diazotrophic bacteria, symbiotic or free-living, play an important role in biological nitrogen fixation and supply of this primary nutrient to plants, including rice. The conservation process of these microorganisms is essential to meet the demands of agricultural research and must guarantee the maintenance of the original characteristics of the isolates, free from mutations. Bacterial isolates preserved in the laboratory must maintain their original characteristics and be free from mutations. This work aimed to evaluate methods for preservation, and perform molecular characterization by the presence of nifs D and H genes, in bacterial isolates important in biological nitrogen fixation for rice. A comparison was made between the methods of preservation of microorganisms in order to detect which one ensures the viability, morphology, physiology and genetics of the isolates, keeping the culture viable for a long time in isolates from the Collection of Phytopathogenic Microorganisms “Profº. Gilson Soares da Silva – MGSS” from the Phytopathology Laboratory, State University of Maranhão. As for the characterization of genetic variability, grouping methods among the isolates were tested, aiming at the formation of groups with the greatest genetic distance identified. To confirm the presence of the nif gene in the genome of the isolates, specific primers were used, and the sequences obtained were validated and compared with the National Center for Biotechnology Information (NCBI) nucleotide database. Cryopreservation confers the best preservation of the isolates and, as for the conservation of the isolates, they remained with survival, stable and pure in the face of preservation methods, maintaining their genetic and phenotypic configurations and specificities. The isolates showed high similarity rates for the nifD and nifH genes of the Pseudomonas genus. This type of study is important to contribute to research related to DNA analysis and genetic mapping, and to emphasize the importance of maintaining living collections for phylogenetic studies.